Food subsidy programs and the health and nutritional status of disadvantaged families in high income countries: a systematic review - Black Andrew P; Brimblecombe Julie; Eyles Helen; Morris Peter; Vally Hassan; O'Dea Kerin (BMC, 2012)
Abstract Background Less healthy diets are common in high income countries, although proportionally higher in those of low socio-economic status. Food subsidy programs are one strategy to promote healthy nutrition and to reduce socio-economic inequalities in health. This review summarises the evidence for the health and nutritional impacts of food subsidy programs among disadvantaged families from high income countries. Methods Relevant studies reporting dietary intake or health outcomes were identified through systematic searching of electronic databases. Cochrane Public Health Group guidelines informed study selection and interpretation. A narrative synthesis was undertaken due to the limited number of studies and heterogeneity of study design and outcomes. Results Fourteen studies were included, with most reporting on the Special Supplemental Nutrition Program for Women, Infants and Children in the USA. Food subsidy program participants, mostly pregnant or postnatal women, were shown to have 10-20% increased intake of targeted foods or nutrients. Evidence for the effectiveness of these programs for men or children was lacking. The main health outcome observed was a small but clinically relevant increase in mean birthweight (23-29g) in the two higher quality WIC studies. Conclusions Limited high quality evidence of the impacts of food subsidy programs on the health and nutrition of adults and children in high income countries was identified. The improved intake of targeted nutrients and foods, such as fruit and vegetables, could potentially reduce the rate of non-communicable diseases in adults, if the changes in diet are sustained. Associated improvements in perinatal outcomes were limited and most evident in women who smoked during pregnancy. Thus, food subsidy programs for pregnant women and children should aim to focus on improving nutritional status in the longer term. Further prospective studies and economic analyses are needed to confirm the health benefits and justify the investment in food subsidy programs.